2016
DOI: 10.1242/jcs.176479
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of newly synthesized proteins to proteostasis stress

Abstract: The capacity of the cell to produce, fold and degrade proteins relies on components of the proteostasis network. Multiple types of insults can impose a burden on this network, causing protein misfolding. Using thermal stress, a classic example of acute proteostatic stress, we demonstrate that ∼5-10% of the soluble cytosolic and nuclear proteome in human HEK293 cells is vulnerable to misfolding when proteostatic function is overwhelmed. Inhibiting new protein synthesis for 30 min prior to heat-shock dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Therefore, it is likely that these proteins self-assemble into amyloid structures directly from the unfolded state occurring during or shortly after translation rather than undergoing unfolding from their natively folded state prior to amyloid formation. This is consistent with protein folding intermediates being particularly at risk of aggregating as exemplified by a recent study revealing that newly synthesized proteins constitute the majority of the insoluble fraction prompted by thermal stress (31). Furthermore, artificially increasing ribosome pausing during translation causes widespread protein aggregation (9).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is likely that these proteins self-assemble into amyloid structures directly from the unfolded state occurring during or shortly after translation rather than undergoing unfolding from their natively folded state prior to amyloid formation. This is consistent with protein folding intermediates being particularly at risk of aggregating as exemplified by a recent study revealing that newly synthesized proteins constitute the majority of the insoluble fraction prompted by thermal stress (31). Furthermore, artificially increasing ribosome pausing during translation causes widespread protein aggregation (9).…”
Section: Discussionsupporting
confidence: 81%
“…In addition to pre-existing proteins, newly synthesised polypeptides are particularly vulnerable and damaged under proteotoxic stress 33 . Treatment of cells with the translational inhibitor Cycloheximide (CHX) prevented the increase in protein NEDDylation upon HS, indicating that the NEDD8 response to proteotoxic stress depends on protein synthesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is unclear what fraction of the mammalian proteome denatures and misfolds during heat stress (Wallace et al 2015), the level of ubiquitylated proteins rapidly increases in stressed cells (Fujimuro et al 1997), suggesting that degradation of misfolded proteins via the UPS is critical in reestablishing proteome balance (Parag et al 1987). Nascent polypeptides synthesized prior to heat stress, possibly still bound to ribosomes in unfolded states, are thought to represent the major vulnerable fraction of the proteome that is targeted for degradation (Medicherla and Goldberg 2008;Xu et al 2016). A comprehensive genome-wide deletion screen for induction of the HSR in yeast (Brandman et al 2012) under nonstress conditions revealed an enrichment of individual chaperones and members of the UPS, among other inducers, pointing to a strong cross talk between the two PN modules.…”
Section: Stress Response Pathwaysmentioning
confidence: 99%